The emerging role of Toxoplasma gondii in periodontal diseases and underlying mechanisms - Cao, Henglong; Lin, Jianfeng; Yuan, Hao; Yang, Zipeng; Nie, Min; Pathak, Janak L.; Yuan, Zi-Guo; Yu, Miao (Frontiers in Immunology, 2024)
Toxoplasma gondii (T. gondii), an obligate intracellular protozoan parasite, is increasingly recognized for its role in various human diseases, including periodontal diseases. Periodontal diseases comprise a wide range of inflammatory conditions that not only affect the supporting structures of the teeth and oral health but also contribute to systemic diseases. The parasite's ability to modulate the host's immune response and induce chronic inflammation within the periodontium is a key factor in periodontal tissue damage. Through its virulence factors, T. gondii disrupts the balance of inflammatory cytokines, leading to dysregulated immune responses, and exacerbates oxidative stress in periodontal tissues. And T. gondii invasion could affect specific proteins in host cells including HSP70, BAGs, MICs, ROPs, SAGs, and GRAs leading to periodontal tissue damage. The indirect role of the host immune response to T. gondii via natural killer cells, monocytes, macrophages, neutrophils, dendritic cells, T cells, and B cells also contributes to periodontal diseases. Understanding these complex interactions of T. gondii with host cells could unravel disease mechanisms and therapeutic targets for periodontal diseases. This review delves into the pathogenic mechanisms of T. gondii in periodontal diseases, offering a detailed exploration of both direct and indirect pathways of its impact on periodontal health.